2022
DOI: 10.1007/s10493-022-00703-0
|View full text |Cite|
|
Sign up to set email alerts
|

An evaluation of errors in the mitochondrial COI sequences of Hydrachnidia (Acari, Parasitengona) in public databases

Abstract: All DNA sequences used in this study were obtained from GenBank and BOLD public databases. The COI sequence alignment and phylogenetic tree are provided as Supporting Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…An example of misidentification is the chloroplast genome of Chenopodium album (GenBank accession No. MF418659) (de Brito et al 2015; Park et al 2021b; Peláez et al 2022; Pentinsaari et al 2020). A phylogenetic tree constructed from the complete mitochondrial genomes suggested that each species was distributed in a different clade.…”
Section: Resultsmentioning
confidence: 99%
“…An example of misidentification is the chloroplast genome of Chenopodium album (GenBank accession No. MF418659) (de Brito et al 2015; Park et al 2021b; Peláez et al 2022; Pentinsaari et al 2020). A phylogenetic tree constructed from the complete mitochondrial genomes suggested that each species was distributed in a different clade.…”
Section: Resultsmentioning
confidence: 99%
“…The number of specialists must therefore be maintained, and the discipline must remain alive in the academic world, if we want to maintain these skills. Since the initial identification of the sequenced specimen is correct, DNA barcoding is an efficient way to assign unidentified specimens to known species but the number of errors should not be underestimated [28,29]. Deep learning technologies constitute interesting ways to implement automatic species recognition from pictures [30].…”
Section: Discussionmentioning
confidence: 99%